Multiple-output production modeled with three functional forms - Villezca Becerra, Pedro Antonio; Richard Shumway, C. (Western Agricultural Economics Association, 1992)
Aggregate dual models are specified to examine multiple-output production relationships in each of four major, geographically dispersed, agricultural states (California, Iowa, Texas, and Florida). Three locally-flexible functional forms (translog, generalized Leontief, and normalized quadratic) are employed to conduct analytic simplification tests, estimate systems of output supply and input demand equations consistent with nonrejected hypotheses, derive elasticities, and determine to what extent analytic simplification tests and policy-relevant results are sensitive to functional form and state. Important differences in empirical implications were found due both to functional form and geographic unit, but differences were greater for the latter